INTERNATIONAL COLLABORATION IN PUBLIC EDUCATION ORGANIZATION PPPPTK BOE Malang Case Study - Nurmala, Citrawiri (Jurnal Ilmiah Administrasi Publik, 2013)
Abstract: International Collaboration In Public Education Organization Pppptk Boe Malang Case Study. Vocational education has been considered as one option in order to solve some problems in the matter of economic and social development which able to produce âready to workâ graduates.Â Â  Thus, over decades the vocational education quality improvements has been continuously and seriously done. The purpose of the research is to study about the international collaboration implementation between vocational public education organizations with industries, education organizations and NGOs. In this research, the writer uses qualitative research method the model of international collaboration implementation of PPPPTK BOE Malang as the public vocational education organization under the ministry of education and culture. Â The result of the research is expected to be useful as the decision making reference for other public vocational education in Indonesia, and possibly in the world, of how such international collaboration could be implemented and brought benefits to the service quality development. Keywords: Collaboration, Public organization, PPPPTK BOE Malang, Vocational education Â  Abstrak: Kolaborasi internasional Dalam Pendidikan Umum Organisasi PPPPTK Boe Studi Kasus Malang. Pendidikan kejuruan telah dipandang sebagai salah satu pilihan pemecah masalah yang terkait dengan masalah ekonomi dan kesejahteraan sosial karena mampu menghasilkan lulusan-lulusan yang âsiap kerja.â Oleh karena itu, selama kurun waktu beberapa dekade, penyempurnaan kualitas pendidikan kejuruan telah secara terus-menerus dan serius dilakukan. Tujuan dari penelitian ini adalah untuk meneliti mengenai pelaksanaan kerjasama internasional antara institusi-institusi pendidikan kejuruan publik dengan partner industri, institusi-institusi pendidikan lain, dan lembaga swadaya masyarakatl. Dalam penelitian ini, penulis menggunakan model pelaksanaan kerjasama internasional yang dilaksanakan oleh PPPPTK BOE malang sebagai salah satu institusi pendidikan kejuruan publik dibawah naungan kementerian pendidikan dan kebudayaan. Hasil dari penelitian ini diharapkan dapat digunakan menjadi referensi dalam proses pengambilan keputusan lembaga pendidikan kejuruan publik yang lain di Indonesia dan di dunia mengenai bagaimana model kerjasama internasional seperti itu dapat dilaksanakan dan memberikan keuntungan terhadap peningkatan kualitas pelayanan. Â  Kata Kunci: Kerjasama, Institusi publik, PPPPTK BOE Malang, Pendidikan kejuruan